Math, asked by kiyadaiya, 7 months ago

(5a³+6a⁴+3a²-9+5a)÷(a²-1)​

Answers

Answered by tarracharan
10

\bold{Hope\: this\:helps\:you.}

Attachments:
Answered by pulakmath007
9

SOLUTION

CORRECT QUESTION

TO DETERMINE

 \displaystyle \sf{ \frac{5 {a}^{3} + 6 {a}^{4} + 3 {a}^{2}  - 9 - 5a  }{ {a}^{2}  - 1} }

EVALUATION

Here the given fraction is

 \displaystyle \sf{ =  \frac{5 {a}^{3} + 6 {a}^{4} + 3 {a}^{2}  - 9 - 5a  }{ {a}^{2}  - 1} }

Which can be rewritten as

 \displaystyle \sf{  = \frac{6 {a}^{4} +5 {a}^{3} +  3 {a}^{2}  - 5a   - 9}{ {a}^{2}  - 1} }

Now Numerator

 \sf{ = 6 {a}^{4} +5 {a}^{3} +  3 {a}^{2}  - 5a   - 9}

For a = 1 the value of numerator is zero

∴ ( a - 1 ) is a factor of the numerator

 \sf{ 6 {a}^{4} +5 {a}^{3} +  3 {a}^{2}  - 5a   - 9}

 \sf{  = 6 {a}^{4}  - 6 {a}^{3} +11 {a}^{3}  - 11 {a}^{2}  + 14 {a}^{2}  - 14a + 9a   - 9}

 \sf{  = 6 {a}^{3}(a - 1)   +11 {a}^{2} (a - 1)    + 14a(a  -1) + 9(a   - 1)}

 \sf{  =(a - 1) (6 {a}^{3}   +11 {a}^{2}    + 14a+ 9)}

 \sf{  =(a - 1) (6 {a}^{3} + 6 {a}^{2}    +5 {a}^{2}   + 5a  + 9a+ 9)}

 \sf{  =(a - 1)  \bigg[6 {a}^{2} (a + 1)   +5a(a + 1)  + 9(a+1 ) \bigg] }

 \sf{  =(a - 1) (a + 1) (6 {a}^{2}    +5a  + 9 ) }

 \sf{  =( {a}^{2} - 1)  (6 {a}^{2}    +5a  + 9 ) }

Hence

 \displaystyle \sf{ \frac{5 {a}^{3} + 6 {a}^{4} + 3 {a}^{2}  - 9 - 5a  }{ {a}^{2}  - 1} }

 \displaystyle \sf{  = \frac{6 {a}^{4} +5 {a}^{3} +  3 {a}^{2}  - 5a   - 9}{ {a}^{2}  - 1} }

 \displaystyle \sf{  = \frac{({a}^{2}  - 1)  (6 {a}^{2}    +5a  + 9 )}{ {a}^{2}  - 1} }

 \displaystyle \sf{  =   (6 {a}^{2}    +5a  + 9 ) }

━━━━━━━━━━━━━━━━

Learn more from Brainly :-

1. divide : (4x²- 100) ÷ 6(x+5)

https://brainly.in/question/15559404

2. 6x2 + x - 15 is divided by 3x + 5.

In each case, verify your answer.

https://brainly.in/question/17277773

Similar questions